Renewable energy from small and micro hydro project : practical aspects and case studies - Awasthi, Shambhu Ratan; Pandey, Shiv Vishal (New Delhi TERI, 2021)
Energy production and utilization are directly associated with climate change. Harnessing energy from renewables can provide a viable path towards achieving sustainability and reducing carbon footprints, which can help mitigate the harmful effects of climate change. India is endowed with substantial hydropower potential. Under this light, Renewable Energy from Small and Micro Hydro Projects: practical aspects and case studies introduces the process of developing hydropower projects, especially in Indian context. The role of hydroelectric power, as part of water management, in combating climate change also forms the subject matter of this book. Selection of suitable sites, hydro turbines, electrical systems, transportation, and salient features of dam and reservoir operation are discussed. Cost estimation, feasibility studies, promotional policies of the government, and other organizations involved in hydropower also form the subject matter of the title. The publication also covers the basics of fluid mechanics along with an overview of the hydropower development in India and the world. The book is supplemented with statistical data relevant to development and operation of hydropower projects which makes the text an authentic read. It will be a useful guide and reference to students, designers, planners, consultants, and field engineers engaged in hydro energy sector.
Keywords: Micro hydro project; Energy